Imaging Modalities in Assessment of Gynecological Causes of Acute Pelvic Pain at Shifa Medical Complex: A Cross-sectional Study - Mohsen, Mohammed; Auda, Basel (International Journal of Innovative Research in Medical Science, 2024)
Background: Acute pelvic pain in women often necessitates prompt and accurate diagnosis to initiate appropriate treatment. Imaging modalities such as ultrasound, MRI, and CT scans play crucial roles in identifying underlying gynecological causes. Methods: This cross-sectional study was conducted at Shifa Medical Complex, Gaza, Palestine, involving 181 female patients aged 18 years and above presenting with acute pelvic pain. Data collection included demographic details, clinical symptoms, and imaging findings from ultrasound, MRI, and CT scans. Statistical analyses, including chi-square tests and diagnostic performance metrics, assessed the associations and diagnostic accuracy of imaging modalities. Results: Most participants were young adults (mean age 26.99 ± 5.81 years) predominantly without significant medical conditions (93.3%). Ultrasound revealed normal findings in 34.8% of cases, followed by uterine fibroids (23.2%) and ovarian cysts (17.1%). MRI identified uterine fibroids (31.7%) and endometriosis (26.7%) as predominant, while CT scans highlighted adnexal masses (30.0%) and ectopic pregnancies (22.5%). Significant associations (p < 0.05) were found between imaging diagnoses and clinical symptoms such as dyspareunia and dysmenorrhea. Diagnostic accuracy metrics showed ultrasound with sensitivity of 86.4%, specificity of 78.2%, and positive predictive value (PPV) of 81.6%; MRI with sensitivity of 92.5%, specificity of 85.3%, and PPV of 88.7%; and CT scan with sensitivity of 78.9%, specificity of 71.4%, and PPV of 74.6%. Conclusion: Imaging modalities, particularly MRI, demonstrated high sensitivity and specificity in diagnosing gynecological causes of acute pelvic pain. These findings underscore the importance of utilizing appropriate imaging techniques for accurate and timely management of patients presenting with acute pelvic pain.